A practical guide to data mining for business and industry - Ahlemeyer-Stubbe, Andrea (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
"Data mining is well on its way to becoming a recognized discipline in the overlapping areas of IT, statistics, machine learning, and AI. Practical Data Mining for Business presents a user-friendly approach to data mining methods, covering the typical uses to which it is applied. The methodology is complemented by case studies to create a versatile reference book, allowing readers to look for specific methods as well as for specific applications. The book is formatted to allow statisticians, computer scientists, and economists to cross-reference from a particular application or method to sectors of interest."--
8.1 Recipe 1: Response Optimisation: To Find and Address the Right Number of Customers8.2 Recipe 2: To Find the x% of Customers with the Highest Affinity to an Offer; 8.3 Recipe 3: To Find the Right Number of Customers to Ignore; 8.4 Recipe 4: To Find the x% of Customers with the Lowest Affinity to an Offer; 8.5 Recipe 5: To Find the x% of Customers with the Highest Affinity to Buy; 8.6 Recipe 6: To Find the x% of Customers with the Lowest Affinity to Buy; 8.7 Recipe 7: To Find the x% of Customers with the Highest Affinity to a Single Purchase
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Data mining; Marketing -- Data processing; Management -- Mathematical models; COMPUTERS -- General; Data mining; Management -- Mathematical models; Marketing -- Data processing; Marketing - Data processing; Electronic books; Electronic books